(3GdMcheI GdEdcJQhfjI hOhQgG aj JbOje GdNOeGJ GdeQabjI (B/s - (3GdMeGOI, MeRI VGMjs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2016)
(3jJfGhd cJGH (B((3GdMcheI GdEdcJQhfjI hOhQgG aj JbOje GdNOeGJ GdeQabjI(B) (3hGdPj bGe HJCdjag (B"(3MeRI VGMj GdMeGOI(B" (3aj MhGdj (B(230) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdeQGab GdYGeI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdJegjOj (B: (3GdMcheI GdEdcJQhfjI hGdCSHGH GdQFjSI dJWHjbgG aj Xd GfJTGQ THcI GdEfJQfJ, GdaUd GdChd (B: (3GdJMhd fMh GdMcheI GdEdcJQhfjI, GdaUd GdKGfj (B: (3GdNOeGJ GdeQabjI GdJj JbOegG GdMcheI GdEdcJQhfjI hJLGQH GdOhd aj JWHjbgG(B.s
(3edGMb (B: (3UaMI (B185-211.s
(3eUWdMGJ (B: (3UaMI (B210-212s
(3HHdjhLQGajI (B: (3UaMI (B213-224.s
Keywords: (3GdeQGab GdYGeIs -- (3bhGfjf hJTQjYGJs; (3GdeQGab GdYGeIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdeQGab GdYGeIs -- (3bhGfjf hJTQjYGJs -- (3ShQjGs; (3GdEfJQfJ aj GdEOGQI GdYGeIs -- (3eUQs; (3GdEfJQfJ aj GdEOGQI GdYGeIs -- (3ShQjGs